2010
DOI: 10.1007/s11418-010-0490-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of 1H-NMR spectroscopy to validation of berberine alkaloid reagents and to chemical evaluation of Coptidis Rhizoma

Abstract: Berberine, palmatine, and coptisine are major pharmacologically active protoberberine alkaloids in Coptidis Rhizoma, and have been used as indices for chemical evaluation of the crude drug. (1)H-NMR spectroscopy was applied to determination of purities of commercial reagents of protoberberine alkaloids. The purities of the alkaloids were calculated from the ratios of the intensities of the H-13 singlet signal at about δ 8.7 ppm of target protoberberine alkaloids to integration of a hexamethyldisilane (HMD) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Furthermore, qHNMR spectroscopy is rapid and non-invasive, and in most cases it does not require laborious sample pre-cleaning steps. 11) In the present investigation, we demonstrated that qHNMR spectroscopy can be effectively applied for the quantitative determination of carthamin in commercial preparations of Carthamus Red without an authentic carthamin sample.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, qHNMR spectroscopy is rapid and non-invasive, and in most cases it does not require laborious sample pre-cleaning steps. 11) In the present investigation, we demonstrated that qHNMR spectroscopy can be effectively applied for the quantitative determination of carthamin in commercial preparations of Carthamus Red without an authentic carthamin sample.…”
mentioning
confidence: 59%
“…NMR spectroscopy acquisition and processing were performed as previously described. 11) In brief, eight scans were performed for each sample with a 90° pulse and a 30-s pulse delay because high precision qHNMR spectra can be achieved when the pulse angle is 90° and the pulse delay time is greater than the quintuple spin-lattice relaxation time (>5*T 1 ). The chemical shifts are given as δ values (ppm) relative to the internal standard HMD.…”
Section: Methodsmentioning
confidence: 99%
“…The combined ethyl acetate extract was concentrated under reduced pressure to yield the aglycone. The purity of each aglycone thus obtained was estimated by quantitative 1 H NMR analysis (Hasada et al, 2011). Geniposide, genipin, and loganin were obtained from Wako Pure Chemicals and secologanin from Sigma-Aldrich.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In a previous paper, we reported the quantitative determination of the components of crude drugs by proton-specific quantitative NMR ( 1 HqNMR) [12][13][14][15][16]. The 1 H-qNMR method has various advantages over other quantitative methods, including HPLC.…”
Section: Introductionmentioning
confidence: 99%